Choice of pollen donor affects weight but not composition of Actinidia chinensis var. chinensis 'Zesy002' (Gold3) kiwifruit. Issue 2 (3rd April 2018) - Seal, Alan G.; Clark, Christopher J.; Sharrock, Keith R.; de Silva, Handunnethi Nihal; Jaksons, Peter; Wood, Megan E.
ABSTRACT: Flowers of Gold3 kiwifruit ( Actinidia chinensis var. chinensis 'Zesy002', marketed as Zespri® SunGold Kiwifruit) were hand pollinated with pollen from different A. chinensis var. chinensis and A. chinensis var. deliciosa males. Fruit were evaluated for weight, firmness, dry matter content, soluble solids content, seed weight and seed number. Fourier Transform Infrared (FTIR) spectroscopy was used to estimate titratable acidity and the concentrations of the major fruit sugars and acids. Fruit from pollination by male cultivar M43 weighed significantly less than those from pollination by males M91 and M33. These differences could be explained by variation in total seed number between pollen treatments. However, the choice of pollen donor from among those tested appeared to have little impact on Gold3 fruit composition. Regardless of the pollen donor, larger fruit tended to have higher sugar and lower acid concentrations.